POWER AND CRITICISM: THE DYNAMICS OF DIGITAL COMMUNICATION IN ONLINE PUBLIC SPACES - Eni Saeni,; RR Roosita Cindrakasih,; Abdul Azis,; Agung Rahardjo,; Jaka Atmaja, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The development of digital communication technology has transformed the landscape of public space into an interactive and participatory arena where power and critique confront each other. This study aims to analyze the dynamics of digital communication in Indonesia's online public space, particularly in the context of the relationship between power and society. Using a descriptive qualitative approach with digital observation (netnography), in-depth interviews, and content analysis, this study explores the phenomenon of public discourse on platforms X (Twitter), Instagram, and TikTok. The results show that power in digital space is hidden and exercised through algorithmic mechanisms and information control. Society, on the other hand, utilizes digital space as a means of resistance through humor, memes, and online activism. The digital public space ultimately becomes an arena for the dialectic between control and freedom, emphasizing the importance of critical digital literacy in maintaining democracy in the information age.